2019
DOI: 10.1161/circulationaha.119.040130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dapagliflozin on Heart Failure and Mortality in Type 2 Diabetes Mellitus

Abstract: Background: In DECLARE-TIMI 58 (Dapagliflozin Effect on Cardiovascular Events–Thrombolysis in Myocardial Infarction 58), the sodium-glucose cotransporter 2 inhibitor dapagliflozin reduced the composite end point of cardiovascular death/hospitalization for heart failure (HHF) in a broad population of patients with type 2 diabetes mellitus. However, the impact of baseline left ventricular ejection fraction (EF) on the clinical benefit of sodium-glucose cotransporter 2 inhibition is unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
445
2
28

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 480 publications
(490 citation statements)
references
References 20 publications
15
445
2
28
Order By: Relevance
“…The DECLARE‐TIMI 58 trial has demonstrated that diabetic HF patients will benefit with dapagliflozin treatment in terms of reduced all‐cause mortality and cardiovascular death in HFrEF. Furthermore, there was also a noted reduction in HF‐related hospitalizations in both HFrEF and HFpEF patients . SGLT2 inhibitors were associated with reductions in HF hospitalizations in diabetic patients .…”
Section: Discussionmentioning
confidence: 86%
“…The DECLARE‐TIMI 58 trial has demonstrated that diabetic HF patients will benefit with dapagliflozin treatment in terms of reduced all‐cause mortality and cardiovascular death in HFrEF. Furthermore, there was also a noted reduction in HF‐related hospitalizations in both HFrEF and HFpEF patients . SGLT2 inhibitors were associated with reductions in HF hospitalizations in diabetic patients .…”
Section: Discussionmentioning
confidence: 86%
“…Between 10–14% of subjects in EMPA‐REG OUTCOME, CANVAS and DECLARE‐TIMI were recorded to have heart failure at baseline by their local investigator. Although hospitalisation for heart failure as an endpoint was blindly adjudicated according to pre‐specified criteria, the diagnostic criteria for heart failure at baseline and the type of heart failure are unknown, although here have been some post hoc attempts to identify information on ejection fraction in DECLARE and CANVAS subjects …”
Section: Dapa‐hfmentioning
confidence: 99%
“…The seventh World Congress on Controversies to Consensus in Diabetes, Obesity, and Hypertension (CODHy 2019) took place in Sorrento, Italy from April 12 to 13. There, Professor Stefano Del Prato provided interesting counterpoints to growing enthusiasm for the use of sodium‐glucose cotransporter 2 (SGLT2) inhibitors in primary prevention, pointing to a recent analysis of the DECLARE‐TIMI 58 trial of dapagliflozin that shows modest benefits of treatment in those without established heart failure. Professor Del Prato first lamented the lack of generalizability of SGLT2 inhibitor cardiovascular (CV) outcomes trials before critiquing the risk‐benefit profile of these treatments in the primary prevention of heart failure.…”
Section: Seventh World Congress On Controversies To Consensus In Diabmentioning
confidence: 99%
“…Professor Del Prato first lamented the lack of generalizability of SGLT2 inhibitor cardiovascular (CV) outcomes trials before critiquing the risk‐benefit profile of these treatments in the primary prevention of heart failure. He used this new analysis of DECLARE of the effects of dapagliflozin on heart failure outcomes in those with and without established heart failure to demonstrate that the absolute risk reduction in primary prevention populations (only 0.5% on heart failure hospitalizations) is troublingly low and raises important questions as to whether such treatment is justified. This absolute risk reduction amounts to a relatively high number needed to treat (NNT) value of 200 that may be impractical in clinical practice.…”
Section: Seventh World Congress On Controversies To Consensus In Diabmentioning
confidence: 99%
See 1 more Smart Citation